Amizade e psicoterapia - Silveira, Ricardo Wagner Machado da (2006)
This work aims at rethinking the therapeutic relationship from the approximations and resonance with the concept of friendship in the works of Foucault, Deleuze, Nietzsche, Derrida, Arendt, Montaigne and Blanchot. The possible neighborhood between friendship and psychotherapy could be evident not only in the dialogues with philosophy but also in the construction of knowledge and practices inspired in experimentation made by Ferenczi and his mutual analysis technique, in the exercise of the clinic of the Therapeutic Accompaniment , in a group clinic, in our experience as a therapist and supervisor of students training on the public mental health system, in our commitment to affirming a clinics political dimension. In this theoretical and practical work we tried to produce shock on the basis of the psychotherapy as it is institutionalized, facing the problematic question/taboo of a neighborhood between friendship relationships and therapeutic relationships. From this problem, it was possible to give consistency to the therapeutic potency of unlimited proximity, as it is present in the texts of Montaigne and his friendship with La Boetie and in the mutuality on the relationship between therapist and patient lived by Ferenczi. On the other hand, we can also state the therapeutic potency of the distance lived as a clash and the fundamental condition of the relationship among friends, as Zaratustra tells us when referring to the enemy as the best friend or on the clash lived between the therapeutic accompanier and his patient when a necessary violence is required. The disruptive potency, and, for the same reason therapeutic of the distance, is on affirming and accepting the alterity as an strategy to break the paralyzing crystallization that capture the subjectivity